Pengaruh Media Sosial Dan Kualitas Layanan Terhadap Loyalitas Konsumen Dengan Reputasi Perusahaan Dan Keputusan Pembelian Sebagai Variable Intervening Pada PT TCI Consulting - Domo Tambunan; Sri Wahyuni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
In the professional or headhunter recruitment services industry, company reputation and service quality are important factors in maintaining trust in consumers. This research aims to examine the influence of social media and service quality on consumer loyalty with company reputation and purchasing decisions as intervening variables at PT TCI Consulting Research This research uses a quantitative approach, where the research sample uses a purposive sampling method with HRD managers/staff who collaborate with PT TCI Consulting totaling 50 people, data analysis uses the SmartPLS 3 application where based on the research results it is found that social media has a significant positive effect on the company's reputation and purchasing decisions but has no effect on consumer loyalty, while service quality has a significant effect on consumer loyalty but has no effect on company reputation and purchasing decisions, company reputation has a positive effect on consumer loyalty while purchasing decisions have no effect on consumer loyalty, company reputation is able to mediate the relationship between the media social media and loyalty but have not been able to mediate the relationship between service quality and loyalty, while purchasing decisions have not been able to mediate the relationship between social media and service quality on loyalty. Keywords: Social Media, Service Quality, Company Reputation, Purchasing Decisions, Consumer Loyalty